Standardisierte Bestimmung tumorinfiltrierender Lymphozyten beim Mammakarzinom - Denkert, Carsten; Loibl, Sibylle; Budczies, Jan; Wienert, Stephan; Klauschen, Frederick (Der Pathologe, 2018)
Background: Tumor-infiltrating lymphocytes (TILs) have been identified as prognostic parameter in breast cancer.ObjectivesThe aim of this review article is to provide an overview on the clinical and analytical validation of TILs in breast cancer.Materials and methodsSummary of international guidelines of the TIL working group as well as clinical and translational studies.Results, ConclusionsBreast carcinomas with a high TIL level have an improved response to neoadjuvant chemotherapy. Triple-negative and HER2-positive carcinomas with increased TIL levels have improved survival. TILs are a new prognostic biomarker for routine histopathological diagnosis.
Gesehen am 11.02.2020